The Outcome of Status Epilepticus and Long-Term Follow-Up - Horváth, László; Fekete, István; Molnár, Márk; Válóczy, Réka; Márton, Sándor; Fekete, Klára (Frontiers in Neurology, 2019)
Objective: This study was to investigate the outcome of status epilepticus (SE) associated with antiepileptic therapy during SE and in follow-up period, risk factors including age, co-morbidities, pre-existing epilepsy, and aetiology in the East-Hungarian region. Methods: A prospective cross-sectional database was compiled from outpatient files between 2013 and 2017. Follow-up ended on 30.06.2018. Results 135 episodes (male: 68, 50.4%) were evaluated, mean age and follow-up time being 64.1±13.9 years and 39.9±14.2 months, respectively. Of the 89 patients with pre-existing epilepsy, 34 failed to visit the outpatient unit regularly. Case fatality rate was 25.2% and 31 patients (30.7%) died after discharge due to co-morbidities; their mean survival time was 10.44±8 months. Focal, generalized and combined type epilepsies were diagnosed in 67 patients (49.6%), 47 patients (34.8%) and 21 patients (15.6%) of SE, respectively. Nine patients had non-convulsive SE (NCSE). Mean seizure-free period was 6.8±6.9 months. Patients taking carbamazepine (20.9%; OR: 0.37, 95%CI: 0.16-0.82; p=0.018), levetiracetam (27.5%; OR: 0.51, 95%CI: 0.27-0.97; p=0.041) or valproate (11.1%; OR: 0.18, 95%CI: 0.05-0.61; p=0.0043) were expected to achieve seizure freedom after SE. The worst outcome was linked to advanced age, aetiology, new onset status epilepticus, NCSE and focal status epilepsy. Conclusion: This study highlights the importance of regular care and patient follow-up.